Relationships between rumen methanogens and fungal communities and their response to changes in alfalfa forms and starch in sheep diets - Guo, Wenliang; Na, Meila; Liu, Shuwei; Li, Kenan; Du, Haidong; Zhang, Jing; Zhang, Yu; Na, Renhua; Liu, Yulan (Frontiers in Microbiomes, 2025)
Alfalfa forms and rumen degradable starch (RDS) levels in diets can profoundly affect growth performance and rumen fermentation patterns, this influence may result in variations in rumen microbiota. However, the effects of RDS levels on methanogenic and fungal communities in alfalfa hay (AH) or alfalfa silage (AS) diets, and the interaction between methanogens and fungi with growth performance and rumen fermentation patterns, remain unknown. In this study, a 2 × 2 factorial design resulted in four diets: two alfalfa forms (AH and AS) and two RDS levels (LR: 14.85% DM RDS; and HR: 20.21% DM RDS). We used 32 female Suffolk sheep for the experiment. On day 75 (including a 15-day transition period and a 60-day trial period), rumen content was collected after slaughter to examine the ruminal methanogens and fungi. The AHHR diet reduced the methanogen Chao 1 index compared to the AS diets (P < 0.05), and the Shannon index was lower than in the ASLR diet (P < 0.05). The fungi Chao 1 index was higher in the AH diets than in the ASHR diet (P < 0.05), and the fungi Shannon index was higher in the LR diets than in the HR diets (P < 0.05). The relative abundance of Aspergillus in the AHLR diet was significantly higher than in the AS diets (P < 0.01), and the relative abundance of Occultifur and Meyerozyma were decreased in the AH diets than in the AS diets (P < 0.05). The LEfSe analysis showed that Methanobrevibacter_sp_YE315 and Methanobrevibacter_sp_AbM4 were enriched in the ASLR diet, while Methanobrevibacter_millerae was enriched in the ASHR diet. For the fungal biomarkers, the AHLR diet included Aspergillus, Metschnikowia, and unclassified_f:Stachybotryaceae; the AHHR diet included stachybotrys, Stemphylium, and Cystobasidium; the ASLR diet included unclassified_k:Fungi, Trichothecium, and Psathyrella; and the ASHR diet included Alfaria. The correlation analysis results showed the relative abundance of Methanobrevibacter, Methanoculleus, Penicillium, Cladosporium, and Exophiala and the concentrations of isobutyrate and isovalerate, which may provide deeper insights into the previously observed differences.